Implementation of Real-Time Offset-Tuning Algorithm for Integrated Corridor Management. Issue 1 (January 2015) - Zhang, Li; Huang, Zhitong; Wen, Yi; Hawkins, Amanda; Fulcher, William Case; Henke, Sarah R.; Roberts, Acey; Zhang, Qi
Integrated corridor management (ICM) has been proved to relieve recurrent and nonrecurrent congestion effectively in a transportation network. Traffic signal coordination is an effective approach for improving travel speed and decreasing delays. The incorporation of traffic signal coordination into ICM further improves the benefits of ICM strategies. However, traffic signal coordination is applied on the basis of commuter traffic, and detour traffic is not considered. A real-time and proactive offset-tuning algorithm is proposed to reduce the delays of detour traffic without disrupting existing traffic. The algorithm explicitly incorporates diverted traffic and diverted traffic patterns into the existing traffic. The offsets of each coordinated intersection are fine-tuned and updated every 10 cycles to provide smooth progression for upcoming traffic. A case study was conducted to prove the effectiveness of the proposed algorithm. The benchmark case was TRANSYT-7F coordinated traffic signal timing plans. The simulation statistics indicated that the proposed approach created a saving of 8.8% in travel time and 8.3% in control delay in the direction of the diversion. The proposed algorithm did not sacrifice the traffic conditions in the opposite direction of the detour. The statistical analysis proved that the average control delay for both the direction of the diversion and the opposite direction, for all intersections, decreased by 5.6%, with a lower control delay at the 95% confidence interval. The diversion contributed to a gain of 9.22 mph or 18.96% in average speed on the freeway.